Block Iterative Algorithms for Solving Hermite Bicubic Collocation Equations - Sun, W. (SIAM journal on numerical analysis, 1996)
In this paper, we present a so-called local elimination technique by which a nonsymmetric system arising in the discretization of the Poisson equation with a Hermite bicubic collocation approximation is reduced to a block tridiagonal and "block symmetric" system. A class of block iterative algorithms is developed for solving the resulting system. The convergence rates of algorithms are discussed.